Listening for Africa : Freedom, Modernity, and the Logic of Black Music's African Origins - García, David F. (Book collections on Project MUSE., 2017)
David F. Garcia examines the work of a wide range of musicians, dancers, academics, and activists between the 1930s and the 1950s to show how their belief in black music's African roots would provide the means to debunk racist ideologies, aid decolonization of Africa, and ease racial violence.